Training on digital footprint management for teenagers in Simo District, Boyolali - Palupi Palupi; Rina Sari Kusuma; Indah Rahmaningsih (Community Empowerment, 2023)
This training is based on the condition that teenagers in Simo District are productive internet users. Concerns are raised on how their digital footprint will impact their future. Teenagers in Simo District are mindful of their digital footprint, but unlikely have awareness of the positive potential of digital footprint. Digital footprint management is essential skill for teenagers to become good online citizen. This community service aims to provides training on how to manage digital footprints to members of PIK Pemuda Kampung KB. The results obtained from this training are that members of PIK Pemuda Kampung KB understand the importance of managing digital footprints as important effort in managing data security as well as to build a positive footprint that will benefit their future.